Morphology of preimaginal stages and taxonomical relationship of Synanthedon spuleri (Fuchs, 1908) (Lepidoptera: Sesiidae) with closely related species in Central Europe - Bąkowski, Marek (Zootaxa, 2013)
The egg, last larval instar, and pupa of Synanthedon spuleri Fuchs are described and illustrated. In Central Europe there is a group of four closely related species including S. spuleri, S. tipuliformis Clerck, S. loranthi Králíček, and S. cephiformis Ochsenheimer. Thus far S. spuleri has been classified as closely related to S. tipuliformis. However, the results of molecular analyses and partly studies of the morphology of the preimaginal stages indicate that S. spuleri is more closely related to S. cephiformis than to S. tipuliformis. In terms of the response of males to similar attractants it appears that S. spuleri is more closely related to S. tipuliformis; however, further research needs to be conducted in this respect.